Computational investigation of hydrogen-induced phonon changes in carbon fiber - Isbill, Sara B.; Brubaker, Zach E.; Shields, Ashley E.; Niedziela, J.L. (Computational materials science, 2023)
[Display omitted] Optical vibrational spectroscopy has shown promise as a noninvasive means of monitoring the mechanical properties of carbon fiber (CF), which is increasingly used for industrial and consumer purposes. However, interpretation of optical vibrational spectra for solid materials is inferential, particularly when defects are present. Because inelastic neutron scattering (INS) spectroscopy is not subject to selection rules, the full vibrational spectra can be measured. And, identifying correlations between INS features and tensile properties can assist in the interpretation of spectra from more commonly used optical vibrational spectroscopic techniques, such as Raman and infrared (IR) spectroscopy. Recent INS experiments on high-performance commercial carbon fibers showed features near 900 and 1100 cm−1 in addition to a broad feature near 3000 cm−1 that increased in intensity with decreasing tensile strength. These features were assigned to hydrogen defects. In the present work, we use density functional theory to simulate the INS spectra of several hydrogen defect geometries in graphite as a model for carbon fiber structure units, confirming the experimental assignment of these peaks to hydrogen modes and providing insights into the structure and lattice dynamics of the defects.